2023
DOI: 10.1002/mds.29426
|View full text |Cite
|
Sign up to set email alerts
|

Intraputamenal Cerebral Dopamine Neurotrophic Factor in Parkinson's Disease: A Randomized, Double‐Blind, Multicenter Phase 1 Trial

Abstract: Background Cerebral dopamine neurotrophic factor (CDNF) is an unconventional neurotrophic factor that protects dopamine neurons and improves motor function in animal models of Parkinson's disease (PD). Objective The primary objectives of this study were to assess the safety and tolerability of both CDNF and the drug delivery system (DDS) in patients with PD of moderate severity. Methods We assessed the safety and tolerability of monthly intraputamenal CDNF infusions in patients with PD using an investigational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In cells, CDNF and MANF localize in the endoplasmic reticulum (ER) (19,20), where they regulate protein homeostasis and ER stress-induced unfolded protein response (UPR) signaling (21)(22)(23)(24)(25). As a potential therapeutic factor for dopamine neurons, CDNF was tested in Phase I-II clinical trials in 17 PD patients, where it was shown to be safe and well tolerated (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…In cells, CDNF and MANF localize in the endoplasmic reticulum (ER) (19,20), where they regulate protein homeostasis and ER stress-induced unfolded protein response (UPR) signaling (21)(22)(23)(24)(25). As a potential therapeutic factor for dopamine neurons, CDNF was tested in Phase I-II clinical trials in 17 PD patients, where it was shown to be safe and well tolerated (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral dopamine neurotrophic factor (CDNF) is a protein with neurotrophic factor properties that has reached its safety and tolerability endpoint in its first phase I/II clinical trials in PD patients (Huttunen et al, 2023;ClinicalTrials.gov identifier: NCT03295786, NCT03775538). CDNF is a 161 amino acid long protein, endogenously present in the brain and various nonneuronal tissues such as skeletal muscle and testis of both humans and mice (Lindholm et al, 2007).…”
Section: Introductionmentioning
confidence: 99%